PENURUNAN KADAR MINYAK DAN COD AIR LIMBAH OPERASIONAL PEMBANGKIT LISTRIK DENGAN FLOTASI DAN LUMPUR AKTIF - I Wayan Budiarsa Suyasa (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractResearch about treatment of waste water power plant operation of PT Indonesia Power atDenpasar with the flotation and activated sludge method has been carried out. The objectiveof research is determine optimum treatment time in flotation and activated sludge todecrease oil and COD content of wastewater. In the flotation stage, 8 liters of waste waterpower plant operation of PT Indonesia Power aerated by aerators for 60 minutes. After theflotation treatment waste water treated by activated sludge method for 24 hours. Theresults of research showed that the time of treatment in the 60th minute the flotation processcapable to reduce the oil contents reach 450 mg/L with the treatment effectiveness of 97,92%.At the time of treatment in the 24 hours, the activated sludge process has been able toreduce the oil content reach 0 mg/L with treatment effectiveness is 100% and reduce CODvalue reach 27,63 mg/L with the treatment effectiveness of 70,59%. Oil content and CODvalue obtained from are effluent of flotation and activated sludge below Class III WaterQuality according to PerGub Bali Number 8 in 2007 (1 mg/L and 50 mg/L respectively).